The sales process and the paradoxes of trust - Oakes, G. (Journal of business ethics, 1990)
This essay explores a major ethical variable in personal sales: trust. By analyzing data drawn from life insurance sales, the essay supports the thesis that the role of the agent and the exigencies of personal sales create certain antinomies of trust that compromise the sales process. As a result, trust occupies a problematic and apparently paradoxical position in the sales process. On the one hand, success in personal sales is held to depend upon trust. On the other hand, because the techniques required to form trust in personal sales nullify the conditions under which trust is possible, these instruments of trust formation are self-defeating.